Correlation between Students’ Speaking Anxiety and Discussion Activity - Sartika Andi Patau (Sintuwu Maroso Journal of English Teaching, 2019)
One of the factors influence students activity in discussion is speaking anxiety. The objective of the research is to find out whether there is correlation between students’ anxiety and their activity in discussion to fourth semester students in English Education Study Program of Sintuwu Maroso University Poso. The type of the research is quantitative method. The population of the research is the fourth semester students of English Education Study Program. The sample of the research is the population of the research. The data are collected by giving the questionnaire. The data from questionnaire is analyzed by correlation product moment of SPSS 16.0. The result of the research is there is no correlation between students’ activity in discussion and students’ anxiety